DAMPAK PENCAPAIAN PERINGKAT KREDIT'INVESTMENT GRADE' INDONESIA TERHADAP COST OF BORROWING SURAT UTANG NEGARA INDONESIA - Sri Fitriyani; Fiskara Indrawan; Meily Ika Permata; Indriani Karlina (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2012)
In the midst of global uncertainty , the “investment grade” rating achievement at the end of 2011 and early 2012 has boosted optimistic sentiment to the surge of foreign capital flows and the decrease of borrowing cost for domestic investment activities. Empirical studies showed that this achievement would decrease the spread of sovereign bonds significanly along with the decline or probability of default and rise og investor base. Impluse response, using daily taransaction data tested with GARCH method , showed that sovereign spread would drop up to 80bps in 23 days since moody’s announcement on 18 january 2012. The global factor that also has significant influence to spread in global risk indicator. Spread would increase until 30 bps if there was 10 points rise in VIX Index. These results remind us the importance of having strong and resilience economic growth, socio-political, and macroeconomic stability supported by prudent fiscal and monetary policy, external factor sustainability, and improved investment climate.